Penggunaan Metode Particle Swarm Optimization (PSO) pada Optimasi Multirespon Gaya Tekan dan Momen Torsi Penggurdian Material Komposit Glass Fiber Reinforce Polymer (GFRP) yang ditumpuk dengan Material Stainless Steel (SS) - Angga Sateria; Indra Dwi Saputra; Yuli Dharta (Politeknik Manufaktur Negeri Bangka Belitung, 2018)
The Particle Swarm Optimization (PSO) method is one of the methods used for multirespon optimization in the manufacturing process. In this research, the material used is Glass fiber reinforced polymer (GFRP) composite material which is stacked with stainless steel material. The machining process used is a drilling process conducted on a vertical CNC machine Brother TC-22A-O. The thrust force and torque is the response used to evaluate the performance of the drilling process. The quality characteristics of this response